Integrasi Kitab Kuning dalam Kurikulum Pendidikan Agama Islam: Pendekatan Holistik di Ma'had Aly Imam Bukhari - Hanani, Hanif; Haerullah, Haerullah (Lembaga Yasin AlSys, 2024)
This study aims to examine the importance of integrating the traditional Islamic texts known as kitab kuning into the Islamic education curriculum at Ma'had Aly Imam Bukhari. Kitab kuning, which covers fundamental Islamic sciences, is considered essential for providing students with a solid understanding of Islam. The research method used is a case study with a qualitative approach. Data were collected through interviews, participatory observation, and document analysis of the curriculum and teaching activities at Ma'had Aly Imam Bukhari. The findings indicate that kitab kuning forms the core of the educational curriculum at Ma'had Aly Imam Bukhari. Texts such as